Chromosome-Scale Genome of Masked Palm Civet (Paguma larvata) Shows Genomic Signatures of Its Biological Characteristics and Evolution - Lan, Tianming; Fang, Dongming; Li, Haimeng; Sahu, Sunil Kumar; Wang, Qing; Yuan, Hao; Zhu, Yixin; Yang, Zipeng; Zhang, Le; Yang, Shangchen; Lu, Haorong; Han, Lei; et al. (Frontiers in Genetics, 2022)
The masked palm civet (Paguma larvata) is a small carnivore with distinct biological characteristics, like omnivorous diet and also serve as the vector of pathogens. Although this species is not an endangered animal, its population is reportedly declining. Since the SARS epidemic in 2003, the public has been particularly concerned about this species.Here, we present the first genome of the P. larvata, comprising 22 chromosomes assembled using single tube long fragment read (stLFR) and Hi-C technologies. The genome length is 2.41 Gb with a scaffold N50 of 105.6 Mb. We identified the 107.13 Mb X chromosome and one 1.34 Mb Y-linked scaffold and validated by resequencing 45 P. larvata individuals. We predicted 18,340 protein-coding genes, among which 18,333 genes were functionally annotated. Interestingly, several biological pathways related to immune defenses were found to be significantly expanded. Also, more than 40% of the enriched pathways on the positively selected genes were identified to be closely related to the immunity and survival. These enriched gene families were inferred to be essential for the P. larvata to defend against the pathogens. However, we did not find direct genomic basis for its adaptation to omnivorous diet despite multiple attempts of comparative genomic analysis. In addition, we evaluated the susceptibility of the P. larvata to the SARS-CoV-2 by screening the RNA expression of the ACE2 and TMPRSS2/TMPRSS4 genes in 16 organs. Finally, we explored the genome-wide heterozygosity and compared with other animals to evaluated the population status of this species. Taken together, this chromosome-scale genome of the P. larvata provides a necessary resource and insights for understanding the genetic basis of its biological characteristics, evolution and disease transmission control.